Consumption from an Islamic Economic Perspective: Study of Quranic Verses on Consumption - Nanda Kurnia Putra; Amrin Amrin; Mansur Muhammad Abu Zinah; Mowafg Masuwd; Subhan Subhan (Demak Universal Journal of Islam and Sharia, 2023)
Consumption is a primary need in human daily life to be able to sustain life. Consumption that is carried out by the rules of sharia, is permissible in religion. The purpose of this study is to analyze the concept of consumption from the perspective of Islamic economics, the study of the verses of the Qur'an about good and correct consumption. This research uses library research methods often also called literature studies, book surveys, or library research. The results of the study concluded that consumption includes all use and utilization of goods and services to meet human needs in everyday life. Several requirements must be met in consumption, including consumption of good (halal) goods, being thrifty, not extravagant, staying away from debt, and staying away from stinginess and stinginess. In the context of Islamic economics, a Muslim is required to consume only good things. Namely halal both halal according to the nature of the substance, how to process it, and how to get it. Consuming only halal goods and services is a form of human obedience to Allah SWT which has implications for getting rewards as a form of blessing from the goods and services consumed. consumption of good goods (halal), thrifty, not extravagant, staying away from debt, staying away from stinginess and stinginess.